Intraocular Concentration of Stem Cell Factor/c-KIT and Galectin-1 in Retinal Diseases - Choi, Yong Je; Kim, Hyeong Min; Na, Tae Young; Park, Kyu Hyung; Park, Sang Gyu; Woo, Se Joon (Investigative Ophthalmology and Visual Science, 2024)
PURPOSE. To investigate the intraocular concentration profiles of stem cell factor (SCF)/cKIT, galectin-1 (GAL-1), and vascular endothelial growth factor (VEGF)-A with regard to retinal disease and treatment response. METHODS. The study group included 13 patients with dry age-related macular degeneration (AMD), 196 with neovascular AMD (nAMD), 21 with diabetic macular edema (DME), 10 with retinal vein occlusion (RVO), and 34 normal subjects with cataracts. Aqueous humor levels of SCF, c-KIT, GAL-1, and VEGF-A were analyzed by immunoassay according to disease group and treatment response. RESULTS. Increased aqueous levels of SCF, c-KIT, and GAL-1 were observed in eyes with nAMD (2.67 ± 3.66, 296.84 ± 359.56, and 3945.61 ± 5976.2 pg/mL, respectively), DME (1.64 ± 0.89, 238.80 ± 265.54, and 3701.23 ± 4340.54 pg/mL, respectively), and RVO (4.62 ± 8.76, 509.63 ± 647.58, and 9079.60 ± 11909.20 pg/mL, respectively) compared with controls (1.13 ± 0.24, 60.00 ± 0.00, and 613.27 ± 1595.12 pg/mL, respectively). In the eyes of nAMD, the levels of all three cytokines correlated positively with VEGF-A levels. After intravitreal injections of anti-VEGF agents, the levels of GAL-1 and VEGF-A decreased significantly, whereas those of SCF and c-Kit showed no significant change. Eyes of nAMD patients with improved vision after treatment had significantly lower levels of c-KIT, GAL-1, and VEGF-A at baseline. CONCLUSIONS. The intraocular levels of cytokines were significantly elevated in eyes with nAMD, DME, and RVO compared to the controls and they showed different response to anti-VEGF treatment. With this result and their known association with angiogenesis, these cytokines may be potential therapeutic targets for future research.
Keywords: Aged; Aged, 80 and over; Angiogenesis Inhibitors; Aqueous Humor; Diabetic Retinopathy; Female; Galectin 1; Humans; Intravitreal Injections; Macular Degeneration; Macular Edema; Male; Middle Aged; Proto-Oncogene Proteins c-kit; Retinal Diseases; Retinal Vein Occlusion; Stem Cell Factor; Vascular Endothelial Growth Factor A; aqueous humor; c-KIT; cytokine; galectin-1; retinal disease